VALUE CONFLICTS IN COMPUTATIONAL MODELING. - Fleischmann, Kenneth R.; Wallace, William A. (Computer (00189162), 2010)
The article presents information on a study conducted to examine the role of value conflicts in computational model design and use by interviewing modelers in the corporate, academic and government laboratories. It states that in the corporate laboratory, one important value conflict that influences the modeling process is the tension between being honest and telling what customers what they want to hear. In an academic laboratory, the need to complete a project on time and the need to do it right is the cause of tension.